0535 Prevalence of various forms of sleep disordered breathing in infants with Down syndrome. (25th May 2022) - Cho, Yeilim; Kwon, Younghoon; Ruth, Chris; Cheng, Samuel; DelRosso, Lourdes
Abstract: Introduction: Children with Down Syndrome (DS) are at high risk of sleep disordered breathing (SDB). Undiagnosed SDB in younger children may confer further risks of cardiovascular and neurocognitive complications associated with DS. However, there is paucity of studies examining SDB in infants with DS. The purpose of the study was to examine the prevalence of obstructive sleep apnea (OSA), sleep hypoventilation (SH) and hypoxemia in infants with DS. Methods: Infants (≤12 months old) with DS who underwent first polysomnography (PSG) at Seattle Children's hospital over a 6-year period were included. Data collected included obstructive apnea hypopnea index (oAHI), central apnea hypopnea index (CAHI), time spent with CO2 levels > 50 mmHg, time (minutes) spent with saturations <88% (T88), and saturation nadir (minO2sat). Exclusion criteria: follow up studies, and studies post procedures. Data presented by descriptive statistics and comparison by unpaired t-test. Results: A total of 526 children with DS underwent PSG during the collection time. Forty two fit criteria (Mean age 6.6 months, male 66%). Diagnostic (n=13), split to oxygen (n=29, 69%). Split studies were more severe when compared with full diagnostic AHI (Mean 44.7 vs. 14.8, p=0.0007), T88 (Mean 12.5 vs. 0.2 p=0.03) and minO2sat (77.6 vs. 85.8%, p=0.01). Overall mean oAHI was 33.7 (S.D. 30) CAI was 3.4 (S.D. 3.1). 5/31 with reliable capnography had SH (16.1%) with no difference in age vs. the non-SH group (6.0 [3.2] vs. 6.6 [3.1], p>0.05). Overall, oAHI was more severe in infants with hypoventilation (58.9 [23.6] vs. 29.3 [63], p>0.05). Ten infants spent >5 min with saturations <88% (21.4%). All infants with hypoxemia had OSA (oAHI Mean 66.5 SD 40). Infants with OSA and hypoxemia had worse oAHI than those without hypoxemia (p<0.05). Conclusion: Our data shows that a large percent of infants with DS (69%) required a split study due to severe OSA (mean oAHI 66.5) or hypoxemia (21.4%). The overall mean AHI for this age group was 33.7. Hypoventilation was present in 16.1%. This study highlights the high prevalence of SDB in infants with DS and supports early PSG assessment in this patient population. Support (If Any):